Costs, Benefits, and Welfare Implications of USAID Investment in Agricultural Research through U.S. Universities. (30th August 2022) - Dalton, Timothy J.; Fuglie, Keith
Abstract: The U.S. Agency for International Development has invested limited funds in international agricultural research through U.S. universities. We present a meta-analysis of impact case studies from this investment. The median net present value of economic impacts at purchasing power parity is PPP$8.4 billion compared to a cumulative investment of US$1.24 billion over 1978–2018. About four-fifths of these economic benefits accrued to individuals with incomes under $5.50/day and about 29% to those in extreme poverty. In addition to these limited case studies evaluating financial benefits and costs, we present several types of additional non-economic benefits.